GAMBARAN HEMODINAMIK INTRA ANESTESI PADA PASIEN GERIATRI YANG MENJALANI HEMIARTHROPLASTY - Marceline Yoa Gusta Astri Utami; Ni Made Anggi Puspiyanti; Eninda Monika; Canthyka Aulia Rahman; M Andri Agatha; Halima Aulia Ita Maghfiroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Geriatric patients undergoing hemiarthroplasty under spinal anesthesia are at high risk of hemodynamic instability. The aging process and the sympathetic blockade effect of spinal anesthesia often trigger complications such as hypotension and bradycardia. This study aims to provide an overview of intra-anesthetic hemodynamic changes in this population. Methods: This descriptive observational study with a case study approach was conducted in five geriatric patients in the Operating Room of Hospital X in January 2026. All patients underwent hemiarthroplasty with spinal anesthesia using 12.5 mg of hyperbaric 0.5% bupivacaine and an opioid adjuvant. Results: All five cases showed a pattern of significant blood pressure decrease (hypotension) in the first 5–10 minutes after spinal anesthesia induction. In addition, recurrent episodes of hypotension were observed during bone cement placement, which indicated Bone Cement Implantation Syndrome (BCIS). Hemodynamic management was carried out with intravenous fluid administration, oxygenation, and the use of vasopressors such as phenylephrine (50–100 mcg) or ephedrine (10 mg). Conclusion: Anesthetic management in geriatric patients requires close hemodynamic monitoring and appropriate pharmacological interventions to address hypotension due to spinal effects and surgical procedures in order to maintain the patient's condition stability until the operation is completed.